RUMAH PINTAR DALAM TAMAN BELAJAR MASYARAKAT (TBM) BERBASIS KEARIFAN LOKAL - Setyowidodo, Irwan; Yulianto, Dema; Handayani, Aprilia Dwi (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. This study is based on the existence of community learning park (in Indonesian, it‟s called Taman Belajar Masyarakat/ TBM), which lacks the attention and participation of the community in the management and development. It supports the authors to study how empirical conditions of community park management and how to develop community learning parks by integrating local cultures and local wisdom. The method used is Participatory Rural Appraisal method and data collection techniques was done by interview, observation, and documentation study. The subject of the study was TBM